Silver nanoparticles as next-generation antimicrobial agents: mechanisms, challenges, and innovations against multidrug-resistant bacteria - Khalifa, Hazim O.; Oreiby, Atef; Mohammed, Temesgen; Abdelhamid, Mohamed A. A.; Sholkamy, Essam Nageh; Hashem, Hamada; Fereig, Ragab M. (Frontiers in Cellular and Infection Microbiology, 2025)
The escalating prevalence of multidrug-resistant (MDR) bacteria presents a critical global health challenge, necessitating the urgent development of alternative antimicrobial strategies. Silver nanoparticles (AgNPs) have emerged as promising antimicrobial agents due to their broad-spectrum activity, unique physicochemical properties, and multiple mechanisms of bacterial inhibition. Their nanoscale size, high surface area-to-volume ratio, and ability to generate reactive oxygen species (ROS) make them highly effective against both Gram-positive and Gram-negative bacteria. AgNPs exert their antimicrobial effects through diverse mechanisms, including membrane disruption, protein and DNA interactions, enzymatic inhibition, and interference with bacterial metabolic pathways. Despite their potent antibacterial activity, concerns regarding bacterial adaptation, cytotoxicity, and non-specific interactions have prompted extensive research into innovative delivery systems to enhance AgNP efficacy while minimizing adverse effects. This review comprehensively explores the synthesis methods and physical properties of AgNPs, emphasizing their antimicrobial mechanisms and emerging resistance patterns. Additionally, we discuss advanced targeted delivery approaches, including surface functionalization, biopolymer encapsulation, liposomal carriers, and stimuli-responsive nanoplatforms, which enhance the stability, selectivity, and controlled release of AgNPs. These strategies not only improve AgNP bioavailability but also reduce host toxicity and prevent bacterial resistance development. Furthermore, we highlight future directions in AgNP-based antimicrobial therapy, such as combinatorial treatments with antibiotics, advanced nanostructure modifications, and the integration of AgNPs into wound dressings, coatings, and biomedical devices. By synthesizing recent advancements, this review underscores the transformative potential of AgNPs as next-generation antimicrobial agents to combat MDR bacterial infections. Addressing the current limitations and optimizing AgNP formulations will be crucial for their successful clinical translation and for mitigating the global antibiotic resistance crisis.